The Role of Genetic Testing in the Clinical Practice and Research of Early-Onset Parkinsonian Disorders in a Hungarian Cohort: Increasing Challenge in Genetic Counselling, Improving Chances in Stratification for Clinical Trials - Illés, Anett; Csabán, Dóra; Grosz, Zoltán; Balicza, Péter; Gézsi, András; Molnár, Viktor; Bencsik, Renáta; Gál, Anikó; Klivényi, Péter; Molnar, Maria Judit (Frontiers in Genetics, 2019)
The genetic analysis of early-onset Parkinsonian disorder (EOPD) is part of the clinical diagnostics. Several genes have been implicated in the genetic background of Parkinsonism, which is clinically indistinguishable from idiopathic Parkinson’s disease. The identification of patient’s genotype could support clinical decision-making process, also track and analyse outcomes in a comprehensive fashion. The aim of our study was to analyse the genetic background of EOPD in a Hungarian cohort and to evaluate the clinical usefulness of different genetic investigations. The age of onset was between 25 and 50 years. To identify genetic alterations, multiplex ligation-dependent probe amplification (n=142), Sanger sequencing of the most common PD associated genes (n=142) and next generation sequencing (n=54) of 127 genes which were previously associated to neurodegenerative disorders were carried out. The genetic analysis identified several heterozygous damaging substitutions in PD associated genes (C19orf12, DNAJC6, DNAJC13, EIF4G1, LRRK2, PRKN, PINK1, PLA2G6, SYNJ1). CNVs in PRKN and SNCA genes were found in five patients. In our cohort nine previously published genetic risk factors were detected in three genes (GBA, LRRK2 and PINK1). In nine cases two or three coexisting pathogenic mutations and risk variants were identified. Advances of sequencing technologies make it possible to aid diagnostics of PD by widening the scope of analysis to genes which were previously linked to other neurodegenerative disorders. Our data suggested, that rare damaging variants are enriched versus neutral variants, among PD patients in the Hungarian population, which raise the possibility of an oligogenic effect. Heterozygous mutations of multiple recessive genes involved in the same pathway may perturb the molecular process linked to PD pathogenesis. Comprehensive genetic assessment of individual patients can rarely reveal monogenic cause in EOPD, although it may identify the involvement of multiple PD associated genes in the background of the disease and may facilitate the better understanding of clinically distinct phenocopies. Due to the genetic complexity of the disease genetic counselling and management is getting more challenging. Clinical geneticist should be prepared for counselling of patients with coexisting disease-causing mutations and susceptibility factors. At the same time genomic-based stratification have increasing importance in future clinical trials.